2021
DOI: 10.1111/jam.15297
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic silver nanoparticle (Bio‐AgNP) has an antibacterial effect against carbapenem‐resistant Acinetobacter baumannii with synergism and additivity when combined with polymyxin B

Abstract: Aims: Carbapenem-resistant Acinetobacter baumannii represents a public health problem, and the search for new antibacterial drugs has become a priority. Here, we investigate the antibacterial activity of biogenic silver nanoparticles (Bio-AgNPs) synthesized by Fusarium oxysporum, used alone or in combination with polymyxin B against carbapenem-resistant A. baumannii. Methods and Results:In this study, ATCC ® 19606 ™ strain and four carbapenemresistant A. baumannii strains were used. The antibacterial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…A novel candidate may be silver nanoparticles (AgNP) that have high therapeutic potential. Several studies have demonstrated their antimicrobial properties, including activity towards multiresistant bacteria (Tang and Zheng 2018;Allend et al 2022) and biofilms of Staphylococcus aureus (Tran and Tran 2021), and activity towards isolates of Prototheca spp. (Jagielski et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A novel candidate may be silver nanoparticles (AgNP) that have high therapeutic potential. Several studies have demonstrated their antimicrobial properties, including activity towards multiresistant bacteria (Tang and Zheng 2018;Allend et al 2022) and biofilms of Staphylococcus aureus (Tran and Tran 2021), and activity towards isolates of Prototheca spp. (Jagielski et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is an opportunistic pathogen with a strong ability to replicate and clone, and its rapid transmission brings about its worldwide prevalence [ 1 , 2 ]. A. baumannii is clinically common and possesses strong environmental adaptability and long survival period [ 3 ]. Multidrug-resistant A. baumannii (MDRAB) is one of the main causes of hospital-acquired infections and critical patient deaths [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could be a great future alternative in bacterial infection control, where smaller doses of these AgNPs are required with the same antibacterial activity [120]. Besides, its combination with polymyxin B showed a 16-fold reduction of the MIC of polymyxin B and decreased carbapenem-resistant Acinetobacter baumannii viability with additive and synergic effects, as well as significantly reduced cytotoxicity towards mammalian Vero cells, indicating its pharmacological safety [121]. The AgNPs synthesized with F. oxysporum f.sp.…”
Section: Metal Nanoparticlesmentioning
confidence: 94%